On some Chebyschev type inequalities in one-sided sense - Zolotarev, V. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. М. Золотарев. Односторонняя трактовка и уточнения некоторых неравенств Чебышевского типа V. Zolotariovas. Kai kurių Čebyševo tipo nelygybių vienpusis traktavimas bei patikslinimai